Oral contraceptive use and malignant melanoma in Australia. - Beral, V; Evans, S; Shaw, H; Milton, G (1984)
In a case control study of 287 women aged 15-24 years with malignant melanoma and 574 matched controls, findings relating to oral contraceptive use and other hormone use are reported. Ever having used oral contraceptives was not associated with an increased risk of melanoma (relative risk for ever use of the pill = 1.0). Women with melanoma were, however, more likely to have taken oral contraceptives for long periods of time in the past, the relative risk associated with oral contraceptive use for a total duration of 5 years or longer which had begun at least 10 years before the melanoma was diagnosed being 1.5 (95% confidence interval 1.03 to 2.14) This elevated risk persisted after controlling for the reported hair and skin colour, frequency of moles on the body, place of birth, and measures of sunlight and fluorescent light exposure. Cases were more likely than controls to have used hormones to regulate their periods, hormonal replacement therapy and be given hormone injections to suppress lactation, the respective relative risks being 1.9, 1.4 and 1.4, but none differed significantly from 1.0. These findings suggest that prolonged oral contraceptive use may, after a lag of 10 years or so, increase the risk of malignant melanoma.